Hydration and outcome in older patients admitted to hospital (The HOOP prospective cohort study) - El-Sharkawy, Ahmed M. (Age Ageing, 2015)
Background: older adults are susceptible to dehydration due to age-related pathophysiological changes. We aimed to investigate the prevalence of hyperosmolar dehydration (HD) in hospitalised older adults, aged ≥65 years, admitted as an emergency and to assess the impact on short-term and long-term outcome. Methods: this prospective cohort study was performed on older adult participants who were admitted acutely to a large UK teaching hospital. Data collected included the Charlson comorbidity index (CCI), national early warning score (NEWS), Canadian Study of Health and Aging (CSHA) clinical frailty scale and Nutrition Risk Screening Tool (NRS) 2002. Admission bloods were used to measure serum osmolality. HD was defined as serum osmolality >300 mOsmol/kg. Participants who were still in hospital 48 h after admission were reviewed, and the same measurements were repeated. Results: a total of 200 participants were recruited at admission to hospital, 37% of whom were dehydrated. Of those dehydrated, 62% were still dehydrated when reviewed at 48 h after admission. Overall, 7% of the participants died in hospital, 79% of whom were dehydrated at admission (P = 0.001). Cox regression analysis adjusted for age, gender, CCI, NEWS, CSHA and NRS demonstrated that participants dehydrated at admission were 6 times more likely to die in hospital than those euhydrated, hazards ratio (HR) 6.04 (1.64–22.25); P = 0.007. Conclusions: HD is common in hospitalised older adults and is associated with poor outcome. Coordinated efforts are necessary to develop comprehensive hydration assessment tools to implement and monitor a real change in culture and attitude towards hydration in hospitalised older adults.